Investigation of emulsion prepared from Endod-based-saponin extract and paraffin oil - Haymanot, Ewunetie (ASTU, 2023)
Endod (Phytolacca Dodecandra) Berries Have Traditionally Been Used As Soap For Washing Cotton Clothes In Ethiopia For Centuries. P. Dodecandra, Locally Called ??Endod??, Produces A Series Of Triterpenoid Saponins That Possess Very Potent And Useful Biological Properties. In This Research, We Used P. Dodecandra Berries For The Extraction Of Saponin As A Biosurfactant. Distilled Water/Ethanol Mixture Was Used For The Extraction Process. The Effect Of Operational Parameters Such As Extraction Time (1-5hr), Extraction Temperature (40-80 ??C) And Ratio Of Sample-To-Solvent (1:5-1:20 G/Ml) Were Evaluated In Terms Of Obtaining High Extraction Yield, Total Saponin. Extracted Saponin Was Mixed With Paraffin Oil For Preparation Of Emulsion. Extracted Saponin Was Characterized Using Properties Such As Foam Stability, Surface Tension, Critical Micelle Concentration (Cmc). It Also Characterized Using Ft-Ir And Nmr Analysis. Emulsification Index Of The Extract Was Also Evaluated. The Optimum Extraction Conditions Were Of Sample To Solvent Ratio Of 1:10g/Ml, Extraction Time Of 3h And Extraction Temperature Of 70 ??C. Cmc Value Of 1.2g/L With 40.04 Mn/M Surface Tension Was Observed. The Most Stable Foam Was Obtained In Presence Of 0.4 Wt% Saponin Solution At Room Temperature. The Presence Of Low Ph Did Not ShowSignificant Effect On Foam Stability At Room Temperature With Cmc Concentration. MoreoverFoam Stability Was Observed As The Temperature Was Raised From Room Temperature To 60??C At Cmc Concentration. Further Increases In Temperature Had Negative Effect On The Stability Of Foam. The Emulsification Index Of The Extracts Was Evaluated At Different Concentrations With Paraffin Oil And Emulsification Activity Was Directly Increased With Concentration Of Extract. The Stability Of Prepared Emulsion Was Checked By Long-Time Storage For 30days. Ft-Ir Analysis Of Extract From The Berries Of P. Dodecandra Revealed That The Existence Of Saponin FunctionalGroup.
Keywords: P. dodecandra, biosurfactant, saponin, surfactant properties of saponin and emulsion